Extending care beyond the clinic: integrating patient-reported outcomes in chronic pain management through human factors engineering - Sadaf Kazi; Sadaf Kazi; Robin Littlejohn; Kelly M. Smith; Kelly M. Smith; Deanna-Nicole Busog; Joseph Blumenthal; Shrey Mathur; Zach McGill; Doug DeBold; Aaron Zachary Hettinger; Aaron Zachary Hettinger; et al. (Frontiers in Health Services)
ObjectivesTapering prescription opioid pain medication through evidence-based guidelines can help in combating the opioid epidemic. Integrating clinical decision support (CDS) into the clinical workflow of tapering can help in translating guidelines to formulate and implement a tapering plan that manages pain symptoms while minimizing withdrawal, and optimally engages with the patient. The purpose of our project was to develop patient- and clinician-facing CDS in the area of chronic pain management in one integrated application (app) called Tapering And Patient Reporting outcomes for Chronic Pain Management (TAPR-CPM) App.MethodsWe leveraged human factors methodologies and a user-centered design (UCD) approach through guideline review, stakeholder interviews, ethnographic workflow analysis, process mapping, design workshops, and usability testing. Participants included patients with chronic noncancer pain, their family members, pain management physicians, primary care physicians, and health IT developers who focus on patient- and provider-facing technologies.ResultsBased on interview findings and workflow analysis, the provider-facing app had five sections: Patient Context, Taper Settings, Create Taper Plan, Withdrawal and Non-opioid Pain Plan, and Summary Dashboard. The patient-facing app had three sections: Maintaining a Pain Journal, Sharing Pain Scores with Provider, and Connecting to Resources about Opioid Tapering.ConclusionsThis project leveraged a multi-method approach based in human factors and UCD to develop the TAPR-CPM app. Engaging with a diverse set of stakeholders including patients, caregivers, primary care providers, pain specialists, and health information technology developers was critical to develop a user-friendly experience with accessible technology to support patient engagement and provider decision-making.